Imaging choroidal osteoma with the Deep Range Imaging Optical Coherence Tomography – a case report - Markiewicz, Anna; Romanowska-Dixon, Bożena; Jakubowska, Barbara; Bogdali, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Choroidal osteoma is a rare, benign tumor which primarily affects young females, occurring at the posterior pole of the eye. Differential diagnosis, based on ophthalmoscopy, ocular ultrasound and modern techniques such as Deep Range Imaging Optical Coherence Tomography, should include amelanotic choroidal melanoma or metastatic tumors. This case report outlines the features of choroidal osteoma imaged using the Deep Range Imaging Optical Coherence Tomography, namely its lamellar and spongy bone structure, sclero-choroidal junction, tumour transparency, parallel horizontal and vertical canals communicating the lesions, as well as the presence of calcified and decalcified regions.